High Sensitivity Integrated Visible to Mid-Infrared Nonlinear Plasmonic Sensor - F. Che; S. A. Ponomarenko; M. Cada; N. Nguyen-Huu (IEEE Photonics Journal, 2017)
We propose a Kretschmann-based nonlinear plasmonic sensor with a gold thin film deposited on a glass prism. Visible and mid-infrared signals are generated in this configuration through the nonlinear processes of sum- and difference-frequency generation, respectively. The calculated maximum sensitivity and figure of merit of our sum-frequency-based sensor is an order of magnitude higher than that of a traditional Kretschmann-based sensor in the visible range. Our difference-frequency-based sensor has a maximum sensitivity of $1.0× 10^{6}$ $\text{nm/RIU}$ in air at 4.29 $μ\text{m}$ , which is three orders of magnitude higher than that of existing devices in the mid-infrared range, with its maximum figure of merit almost two orders of magnitude higher than the alternatives. By comparison, the calculated sensitivity for operation in water for both sum- and difference-frequency is about half that in air. We, thus, demonstrate significant gains in the sensitivity of the well-known Kretschmann-based plasmonic sensor over a wide wavelength range, without modifying the physical sensor, but by exploiting and simply taping the nonlinear optical properties of the system.